Invasive Pests and Their Potential Threats to Indian Agriculture - Keerthana, B.; Rajashekhar, M; Chowdappa, A.; Asritha, Ch.; Priyanka, N.; Bharghavi, K.; Akhil, G.; Viswakarma, K. Rahul (Chronicle of Bioresource Management, 2023)
The Indian agriculture is vulnerable to biotic and abiotic factors mainly invasive pests. These are non-native and exotic which are introduced by humans unintentionally from one region to another. There are about 23 invasive insects recorded in India. They threaten the biodiversity, food security thus significant economic losses. Invasive insects have wide range of characteristics for their establishment and spread viz., wide host range, survival in varied climatic conditions, phenotypic plasticity, high dispersal potential, high fecundity, mutualistic facilitation with viruses and native insects. Climate change and global warming have increased the chances of invasive pests. Government of India have established quarantine stations for monitoring of Invasive Alien Species (IAS). Strict quarantine regulations of import, international trade at the entry points by using molecular diagnostics for early detection will ensure safeguard to India from invasive pest species. Biological control by introduction of natural enemies and chemical control is the last step for the management of the invasive pest.